2020
DOI: 10.1155/2020/4208597
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dexmedetomidine on Tourniquet-Induced Systemic Effects in Total Knee Arthroplasty under Spinal Anesthesia: a Prospective Randomized, Double-Blinded Study

Abstract: Background. Clinical studies on the impact of dexmedetomidine on tourniquet-induced systemic effects have been inconsistent. We investigated the impact of dexmedetomidine on tourniquet-induced systemic effects in total knee arthroplasty. Methods. Eighty patients were randomly assigned to either control (CON) or dexmedetomidine (DEX) group. The DEX group received an intravenous loading dose of 0.5 μg/kg DEX over 10 minutes, followed by a continuous infusion of 0.5 μg/kg/h from 10 minutes before the start of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Choi et al 14 (2019) demonstrated that a dexmedetomidine infusion could prolong the sensory block level in neuraxial anesthesia for TKA, potentially reducing the need for additional postoperative analgesia medications. In addition, Lee et al 15 (2020) asserted that a dexmedetomidine infusion attenuated tourniquet-induced metabolic and coagulation effects and decreased the postoperative opioid requirements for patients undergoing TKA under spinal anesthesia. Dexmedetomidine also has a terminal half-life of approximately 2 hours, but prolonged postoperative sedation may be problematic.…”
Section: Choice Of Anesthetic Techniquesmentioning
confidence: 99%
“…Choi et al 14 (2019) demonstrated that a dexmedetomidine infusion could prolong the sensory block level in neuraxial anesthesia for TKA, potentially reducing the need for additional postoperative analgesia medications. In addition, Lee et al 15 (2020) asserted that a dexmedetomidine infusion attenuated tourniquet-induced metabolic and coagulation effects and decreased the postoperative opioid requirements for patients undergoing TKA under spinal anesthesia. Dexmedetomidine also has a terminal half-life of approximately 2 hours, but prolonged postoperative sedation may be problematic.…”
Section: Choice Of Anesthetic Techniquesmentioning
confidence: 99%